Phenolics from Barleria cristata var. Alba as carcinogenesis blockers against menadione cytotoxicity through induction and protection of quinone reductase - Ali M. El-Halawany; Hossam M. Abdallah; Ahmed R. Hamed; Hany Ezzat Khalil; Ameen M. Almohammadi (BMC, 2018)
Abstract Background There are increasing interests in natural compounds for cancer chemoprevention. Blocking agents represent an important class of chemopreventive compounds. They prevent carcinogens from undergoing metabolic activation and thereby suppressing their interaction with cellular macromolecular targets. Methods The effect of phenolic compounds isolated from Barleria cristata var. alba as chemopreventive agent was evaluated. The ethyl acetate fraction of B. cristata was subjected to different chromatographic techniques for isolation of its major phenolic compounds. The isolated compounds were evaluated for their potential to induce the cancer chemopreventive enzyme marker NAD(P)H quinonereductase 1 (NQO1) in murine Hepa-1c1c7 cell model. Results The ethyl acetate fraction of B. cristata var. alba yielded five known compounds identified as verbascoside (1), isoverbascoside (2), dimethoxyverbascoside (3), p-hydroxy benzoic acid (4), and apigenin-7-O-glucoside (5). Among the tested compounds, isoverbascoside (2) was shown to potently induce the activity of the enzyme in a dose -dependent manner. As a functional assay for detoxification, compound 2 was the strongest to protect Hepa-1c1c7 against the toxicity of menadione, a quinone substrate for NQO1. Conclusion This effect seemed to be attributed to the compound's potential to induce both the catalytic activity and protein expression of NQO1 as revealed by enzyme assay and Western blotting, respectively.